Representation, Otherness and Fantastic Storyworlds: Breaking Gender Binaries and Reworking Identities in Game of Thrones - Coopey, Louise (Imagining the Impossible: International Journal for the Fantastic in Contemporary Media, 2022)
Game of Thrones’ (HBO, 2011-2019) fantastic storyworld incorporates narrative and representational arcs that interrogate its gendered social, cultural and political framework. Working from Schubart and Gjelsvik’s (2016:1) assertion that the show’s female characters are ‘key to the originality […], appeal and popularity of the GoT universe’, I argue that the show capitalizes on fantasy’s position outside the realities and limitations of the human condition. In doing so, it challenges representational binaries through characters like Cersei Lannister (Lena Headey) and Arya Stark (Maisie Williams) from their respective positions within and outside of the structures of power. They push back against the gendered expectations imposed on them by the patriarchal established order, reworking their own identities to forge their own paths. My analysis therefore reflects the scope for a multiplicity of complex identities to emerge within the show and for a deeper understanding of the representational possibilities in television.